The Art of Singing and Playing on the Modern Flute. Volume I: Fundamentals - Castro-Turriago, Jesus Augusto (2024)
The present treatise is a first result of a music research project led by the author in collaboration with The Music, Education, Culture, and Society Research Team. This document realizes a study of the flute extended technique known as Singing and Playing.In describing this technique, this document first presents a complete discussion about various aspects that relate to the Singing and Playing Extended Technique, for example, 1) diverse pedagogical benefits of its regular use; 2) descriptions about basic flute sound and talking/singing making procedures; 3) an exploration of some of the most common graphic notation used to write singing andplaying; 4) a suggested basic instruction for developing this extended technique; 5) inclusion of basic etudes to center the learning of the domain of singing and playing; and, 6) inclusion of the conceptual philosophy behind the treatise. Second, this book presents a complete Singing and Playing method on the modern flute, which studies the basic fundamentals required to master this extended technique.Some of these fundamentals include the practice of major, minor, chromatic, diminish and augmented scales and intervals, and diverse etudes focused on the study of thirds, fourths, fifths and sixths.